Effect of German Merino lambs’ temperament at weaning on certain fattening traits - Pajor, Ferenc; Szentléleki, Andrea; Tőzsér, János; Póti, Péter (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
This study investigated whether temperament at weaning influences fattening traits in lambs. This study concerned with evaluating temperament of German Mutton Merino lambs (n = 51) using temperament test was scored by the temperament score test (behaviour of animals was assessed in a 5-score system (1: calm, 5: nervous) while spending 30 sec on the scale during weighing) at weaning and at the end of fattening. During fattening the lambs fed ad libitum concentrate for 40 days.It was found negative intermediate correlation between the temperament score at weaning and weight at the end of fattening (rrang = -0.50, P < 0.01) and average weight gain (rrang = -0.57, P < 0.01). The weight gain during fattening showed strong (r = 0.85; P < 0.001), the weaning weight showed medium (r = 0.52; P < 0.001) relationship with weight at the end of fattening, whereas it was not relation between weaning weight and weight gain. Therefore, evaluation of temperament at weaning is more successful reason for lambs’ weight gain and weight at the end of fattening compared to weaning weight.
Keywords: temperament; weaning; fattening; lamb; German Mutton Merino